Next generation content delivery infrastructures emerging paradigms and technologies - Fortino, Giancarlo 1971-; Palau, Carlos E. (Premier reference source, 2012)
"This book delivers state-of-the-art research on current and future Internet-based content delivery networking topics, bringing to the forefront novel problems that demand investigation" - Provided by publisher